A complete procedure of ocular prosthesis: A case report - Nafij Bin Jamayet (2018)
Maxillofacial prosthetics includes all the artificial prosthesis that restores missing parts of the face due to trauma, congenital defects or surgically removed, the reason being either malignant, benign neoplasia or trauma. This article describes the rehabilitation of an ocular defect by ocular prosthesis in a male patient whose cause of the defect was ratinoblastoma. Recovery after the loss of an eye requires an adjustment to monocular vision and improvement of the appearance with the use of artificial eyes carefully prepared to match the remaining natural eye. Maxillofacial prosthesis increasesthe patient's quality of life and encourages them to build up their self-confidence to return back to their social life. © 2013 Japan International Cultural Exchange Foundation & Japan Health Sciences University.